Effectiveness of Motivational Interviewing on Self-control, Self-efficacy, and Relapse Rate in Clients Undergoing Substance Abuse Treatment - Taleb Andarz; Isa Mohammadi Zeidi; Saeed Shahsavari; Amin Pakpur (Journal of Health Sciences and Surveillance System)
Background: This study aimed to determine the effect of motivational interviewing (MI) on self-control, self-efficacy, andrelapse rate in clients undergoing substance abuse treatment in Foman city, Iran.Methods: Using a multi-stage random sampling, 72 patients undergoing substance abuse treatment were equally divided into an experimental and control group and participated in this experimental study. Patients participated in eight 45-60- minute motivational interviewing sessions based on Miller’s recommendations. Data were collected before and 3 months after the MI using demographic questions, temptation questionnaire, Tangney’s self-control scale, general self-efficacy scale, and relapse prediction questionnaire (short form).Results: After controlling the effect of the pretest, the mean of temptation significantly decreased in the experimental group after the MI, and the mean of self-efficacy and self-control increased significantly in the experimental group after the MI (P<0.001). In addition, the mean intensity of desire and the probability of consumption improved significantly in the experimental group after MI, after controlling for the pre-test effect (P<0.001).Conclusion: MI is a promising approach to reduce the relapse rate in addicted patients receiving treatment. Therefore, it is suggested that the effectiveness of common drug therapy for successful substance abuse treatment can be increased by including MI in the treatment protocol.